Development scheme for the Traditional Chinese Medicine nursing outpatient clinic (中医特色护理门诊的构建方案及思考) - SU Xiaonan (苏小南); KOU Jialiang (寇嘉靓); LI Yanli (李艳丽); CHEN Yiyun (陈艺芸); YANG Meijie (杨梅洁); JIA Xue (贾雪); CHANG Yan (常燕); MA Zeyun (马泽云); ZHAO Pei (赵培); GAO Ning (高宁) (中西医结合护理)
Traditional Chinese Medicine nursing outpatient clinic is an advanced nursing practice model characterized by the Traditional Chinese Medicine (TCM) culture. Adhering to the principles of holistic view of TCM and nursing by syndrome differentiation, it aims to meet diversified health needs of patients by providing TCM nursing techniques, and plays a unique role in disease prevention and healthcare. It is a continuation of high-quality nursing and embodiment of patient-centered nursing service. The establishment of TCM nursing outpatient clinic is helpful to promote the psychical and mental health of patients, maintain harmonious nurse-patient relationship, promote the specialization and precision in nursing and better meet the health needs of population. This paper summarized the establishment and practice of Traditional Chinese Medicine nursing outpatient clinic, and provided reference for future improvement of TCM nursing outpatient clinic. (中医护理门诊是一种具有中医药文化特色的高级护理实践模式, 以中医整体观和辨证施护为原则, 运用中医特色护理技术, 满足患者多元化的健康需求, 在疾病预防保健中发挥了独特的优势。中医特色护理门诊的开展是优质护理内涵的延续, 体现了以患者为中心的服务理念, 有利于促进患者身心健康, 有利于建立和谐的护患关系, 有利于促使护理学科向专业化、精细化发展, 能够更加满足人民群众的健康需求。本文归纳总结了科室中医护理门诊构建方案及实施经验, 为今后更佳完善中医护理门诊体系提供参考。)